Stereoscopic augmented reality exergame - Bagherian, Behnaz (2018)
Exergaming (also known as active video gaming) is an emerging technology that uses interactive games to increase exercise behavior. Current guidelines for physical activity recommend that children and young people accumulate at least 60 minutes of moderate to vigorous physical activity (MVPA) daily. Unfortunately, many children and adolescents aged 5–18 are not getting their recommended daily dose of MVPA and are thus more prone to obesity and its ill health effects. Furthermore, research shows that children and adolescents are increasingly inactive physically which often associated with poor diet and overweight. This inactively physical has been blamed as one of the leading causes of death. Exergames aim to make exercise more enjoyable, especially for children and young adults who are accustomed to digital technologies. However designing mobile exergames and Augmented Reality interaction has received little scholarly attention. However, most mobile exergames currently either available in the market or in research are focusing on using immersive Virtual Reality The challenge remains that Virtual Reality is only in a virtual environment and AR HMD's are still quite expensive and have their own visual limitations. Also, not much research has been done in the direction of immersive AR exergames that render the camera feed of the real world to stereoscopic vision like VR and overlay AR, using smart phones that can be mounted on the inexpensive headsets like google cardboard or VR box available today. The focus of this research is to develop an immersive AR smart phone exergame that can be used to mount on a google cardboard or VR box like headset and uses the smartphone's camera feed as the real world frame over which AR overlays virtual interactive avatar to motivate the player. The outcome of this research showed the feasibility of this approach (Immersive AR Exergame) and limitations. A prototype of immersive AR Exergame named Stereoscopic Exergame is developed as a proof-of-concept. Evaluation of the prototype application is conducted by testing the application on students and gather the relevant data with questionnaire among them. The research will provide guide lines to future exergame developers who want to provide immersive AR or Mobile AR exergames. The limitations will be hardware enhancement in terms of more convenient, smaller and lighter HMD which is suitable during exercise, and replace phone with small microprocessor which can run the application and will place on top the HMD.